Learning to assist smokers through encounters with standardized patients: An innovative training for physicians in an Eastern European country - Movsisyan, Narine K; Petrosyan, Varduhi; Abelyan, Gohar; Sochor, Ondrej; Baghdasaryan, Satenik; Etter, Jean-François (PLoS One, 2019)
OBJECTIVES: A lack of physician training is a major obstacle for effective tobacco dependence treatment. This study assessed the feasibility of an active learning training program and its effects on smoking cessation counselling skills of medical residents in Armenia, an Eastern European country with high smoking prevalence. STUDY DESIGN: The study used a pre-post assessment of smoking cessation counselling activities and a course evaluation survey to assess the feasibility of the intervention in a different environment. METHODS: We adapted an active learning training model developed in Switzerland. Residents were trained in Yerevan, Armenia, using video-taped counselling sessions, role plays, standardized patients (actors), group discussions and immediate feedback. The training evaluation was done using a semi-structured anonymous questionnaire. The study assessed the physicians' self-reported smoking cessation counselling activities before and 6 months after the training. A non-parametric Mann-Whitney test was used to assess pre-post differences in physicians' counselling skills measured on ordinal scale. RESULTS: Of the 37 residents trained, 75% were female, 89% aged 20-29 years and 83% were never-smokers. Twenty-eight trainees (76%) returned the course evaluation survey and 32 (86%) answered a questionnaire on skills self-assessment at 6 months follow-up. The majority agreed the course was successful in achieving its learning objectives (64%-96%) and increased their confidence in assisting their patients to quit (74%). After 6 months, the physicians were more likely than at baseline to adhere to evidence-based counselling strategies, including assessing the smoking status and dependence and matching the advice to the patient motivation. The training did not, however, improve the prescription of tobacco dependence medications. CONCLUSIONS: Six months after the training, several self-reported smoking cessation counselling activities had significantly improved compared to baseline. This training model is acceptable for medical residents in Yerevan, Armenia and offers a promising approach in addressing the lack of physician counselling skills in similar settings and populations.
Keywords: Program Evaluation; Surveys and Questionnaires; Humans; osoby simulující pacienta ve výuce; Smokers; lidé středního věku; kuřáci; Arménie; studie proveditelnosti; poruchy vyvolané užíváním tabáku; Female; mladý dospělý; dospělí; vzdělávací modely; Models, Educational; Education, Medical, Continuing; lidé; Armenia; poradenství; odvykání kouření; průzkumy a dotazníky; Smoking Cessation; Adult; ženské pohlaví; Tobacco Use Disorder; Male; Middle Aged; lékaři; kontinuální vzdělávání lékařů; Problem-Based Learning; Young Adult; Counseling; hodnocení programu; Feasibility Studies; mužské pohlaví; problémově orientovaná výuka; Physicians; Patient Simulation